Crotalaria ochroleuca as a green manure crop in Uganda - Wortmann, Charles S.; Isabirye, M.; Musa, S (1994)
The potential of Crotalaria ochroleuca check for this species in other resources as a green manure crop was evaluated in a series of on-station and on-farm trials on reddish kaolinitic loam and sandy clay loam soils in Uganda. Production of the green manure by intercropping Crotalaria with either maize or beans was found to be feasible with little reduction in food crop yield and a mean Land Equivalent Ratio of 1.3. The large amounts of N in the Crotalaria indicates that large quantities of N were biologically fixed. Mean maize grain yields following Crotalaria sole crop were 180% and 240% of maize grain yields following maize in two on-station trials and nine on-farm trials, respectively. Mean maize grain yield following bean in rotation were not significantly less compared to maize following Crotalaria, but grain yields were low in both seasons of on-station trials due to adverse conditions. Mean maize stover yield following Crotalaria was 185% of the stover yield when maize followed beans in rotation. In on-farm trials, maize grain yield following Crotalaria was 160% of the maize yield following beans. Bean seed yields in the second season after Crotalaria production were 120 and 150% in plots with Crotalaria in the first season as compared to maize and bean as the first season crop. A green manure of Crotalaria was effective in improving the productivity of the system but there may be opportunities to improve the efficiency of use of the large amounts of nitrogen biologically fixed by the Crotalaria.